Microeconomics - Robert S. Pindyck (Harlow, England Pearson, 2018)
A book that provides a treatment of microeconomic theory that stresses the relevance and application to managerial and public policy decision making.
Keywords: Economics; Business; (MASB2301) Microeconomics